The expanding field of poly(ADP-ribosyl)ation reactions. 'Protein Modifications: Beyond the Usual Suspects' Review Series - Hakmé, Antoinette; Wong, Heng-Kuan; Dantzer, Françoise; Schreiber, Valérie (EMBO reports, 2008)
Poly(ADP-ribosyl)ation is a post-translational modification of proteins that is mediated by poly(ADP-ribose) polymerases (PARPs). Although the existence and nature of the nucleic acid-like molecule poly(ADP-ribose) (PAR) has been known for 40 years, understanding its biological functions--originally thought to be only the regulation of chromatin superstructure when DNA is broken--is still the subject of intense research. Here, we review the mechanisms controlling the biosynthesis of this complex macromolecule and some of its main biological functions, with an emphasis on the most recent advances and hypotheses that have developed in this rapidly growing field.